THE ATACAMA COSMOLOGY TELESCOPE: PHYSICAL PROPERTIES AND PURITY OF A GALAXY CLUSTER SAMPLE SELECTED VIA THE SUNYAEV-ZEL'DOVICH EFFECT - Menanteau, F; Gonzalez, J; Juin, J; Marriage, T; Reese, E; Acquaviva, V; Aguirre, P; Appel, J; Baker, A; Felipe Barrientos, L; Battistelli, E; Bond, JR; et al. (Institute of Physics Publishing, 2010)
We present optical and X-ray properties for the first confirmed galaxy cluster sample selected by the Sunyaev-Zel'dovich effect (SZE) from 148 GHz maps over 455 deg2 of sky made with the Atacama Cosmology Telescope (ACT). These maps, coupled with multi-band imaging on 4 m class optical telescopes, have yielded a sample of 23 galaxy clusters with redshifts between 0.118 and 1.066. Of these 23 clusters, 10 are newly discovered. The selection of this sample is approximately mass limited and essentially independent of redshift. We provide optical positions, images, redshifts, and X-ray fluxes and luminosities for the full sample, and X-ray temperatures of an important subset. The mass limit of the full sample is around 8.0 × 1014 M ⊙, with a number distribution that peaks around a redshift of 0.4. For the 10 highest significance SZE-selected cluster candidates, all of which are optically confirmed, the mass threshold is 1 × 1015 M⊙ and the redshift range is 0.167-1.066. Archival observations from Chandra, XMM-Newton, and ROSAT provide X-ray luminosities and temperatures that are broadly consistent with this mass threshold. Our optical follow-up procedure also allowed us to assess the purity of the ACT cluster sample. Eighty (one hundred) percent of the 148 GHz candidates with signal-to-noise ratios greater than 5.1 (5.7) are confirmed as massive clusters. The reported sample represents one of the largest SZE-selected sample of massive clusters over all redshifts within a cosmologically significant survey volume, which will enable cosmological studies as well as future studies on the evolution, morphology, and stellar populations in the most massive clusters in the universe. © 2010. The American Astronomical Society.